Pemberdayaan Santri melalui Program “Clean Area” di Pondok Pesantren Sunan Drajat Paciran Lamongan - Abdul Mun’im; Moh. Khaeruddin; Desfri Maulana Amkas; A. Khairuddin (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Sunan Drajat Islamic Boarding School is a boarding school located in Banjarwati village, Paciran sub-district which is located in a large complex and is currently in the process of moving towards a clean environment. The Sunan Drajat Islamic Boarding School will later become an example for other pesantren, especially those in Lamongan and East Java in an effort to improve the quality of a clean environment. The obstacles faced are the lack of motivation and awareness of the students about the culture of clean living. So the solution that can be given is to hold a socialization of the